Role of political and social bilateral relations between Sudan and Malaysia in Sudan's economic development - Mohamed Alfaki, Nadir Ahmed (2012)
This thesis examines the role of politics and social bilateral relations between Sudan and Malaysia in the context of Sudan’s economic development within the framework of international relations based on the cooperation between the two countries from 1996-2010. The research thus looks at the political, social and economic ties that have been developed and further examine how the political and social matters between the two countries can influence development of Sudan’s economy. The importance of this bilateral relation between Malaysia and the Government of Sudan (GOS) is probably one of the most significant factors to consider when investigating the economic collaboration between the two countries in terms of trade,development of the oil sector, infrastructural projects and financial assistance. It is very much a symbiotic relationship, where Malaysia is in need of a secure source of oil over the long term, while Sudan needs the external credit, investment and market for its oil. Despite their connection in the Islamic religion and common membership of both countries in organizations such as the Organization of Islamic Conference (OIC) and the Non-Aligned Movement (NAM) and others, there is no strong trade and economic cooperation between the two countries through these organizations. This study attempts to explore the fundamental changes and challenges faced by the two countries and how they can be addressed through economic relations. The basic purpose of this study was three: (a) to investigate the aspects of relationship between Sudan and Malaysia such as cultural and political, (b) to examine how these aspects can strengthen economic relations between the two countries, and (c) to evaluate how Sudan can benefit from Malaysia in terms of economic development based on the bilateral relations between the two countries. Since the subject matter concerns an in-depth study of bilateral relations between the two countries, therefore a qualitative method was deemed more appropriate to undertake such a study using unstructured interview technique and documents to collect the primary and other secondary data. This research was conducted within the framework of Africa-Asia relations and South-South cooperation. The significance of Malaysia’s involvement in facilitating to jump-start Sudan’s economy can be realized through the presence, since 1997, of PETRONAS, Malaysia’s national petroleum company in Sudan’s oil sector. Politically and diplomatically, Sudan and Malaysia have supported each other on issues like human rights in the international arena and Malaysia has been largely instrumental in helping to extend Sudan’s presence internationally, especially within the political grouping of ASEAN. The Sudan-Malaysia bilateral relation over the years has developed to become an outstanding example of a successful South-South cooperation.